Kurdish Teachers and Learners' Preferences and Motivations for Teaching and Learning English through Textbooks or E-learning Platforms - Mohammadkarimi , Ebrahim; Shahbazi, Zoleikha (RADINKA JAYA UTAMA PUBLISHER, 2025)
Traditional textbooks have been replaced by e-learning platforms in English language instruction, and this trend has caused discussions over the effectiveness and motivational impact of each method. The present study explores Kurdish EFL teachers’ and learners’ preferences and motivations for these teaching tools. Using a convergent mixed-methods design, data were collected from 23 teachers and 197 students through questionnaires and interviews. The findings reveal that traditional textbooks are distinctly favored over e-learning platforms due to their structured and focused content, ease of use, and cultural familiarity. The participants’ views of e-learning platforms are influenced by factors such as proficiency level, digital literacy, and access to technology. The study underscores the need for a blended learning approach that combines the strengths of both methods and tackles infrastructural and pedagogical issues to optimize English language instruction in the Kurdish context.